William Morris and the Classical Tradition - Whitla, William (The Routledge Companion to William Morris, 2021)
This chapter outlines William Morris’s often ambivalent relationship to the classics of Greece and Rome by examining five categories: first, his formation in the classics; second, his direct translation of them; third, his adaptations of the classics; fourth, their influence on his polemical writings; and finally, his calligraphic manuscripts of classical writers. Throughout Morris’s education at his public school and at Oxford, the emphasis was almost entirely devoted to the Greek and Latin languages and had almost nothing to do with what was written about, or with historical contexts. Having entered Marlborough College at the age of thirteen in February 1848, only five years after its founding, Morris stood seventh out of fourteen boys at the end of his first term in midsummer 1848. Admitted to an over-crowded Exeter College, Oxford, by the matriculation or entrance examinations of June 1852, Morris was subject to the New Examination Statute of 1850 that mandated three sets of examinations for classics.